Entrepreneurial Resilience and Adaptation in Times of Crisis: A Bibliometric Study on Business Continuity in SMEs - Syahribulan, Syahribulan; Lasaksi, Pardin; Samuddin, Syurwana Farwita; Souisa, Wendy; Hafid, Abdul (Westscience Press, 2024)
This bibliometric analysis investigates the evolving landscape of research on small and medium-sized enterprises (SMEs) focusing on entrepreneurial resilience and adaptation strategies in times of crisis. By utilizing VOSviewer for thematic clusterization and trend analysis, the study maps out the interrelationships among key research themes and tracks their evolution from 2019 to 2022. The analysis identifies foundational themes such as crisis management and performance, alongside emergent themes like digital transformation and gender issues. Furthermore, the research highlights underexplored areas, including the impacts of natural disasters and the role of employees in organizational resilience, presenting potential avenues for future scholarly work. Additionally, an examination of author collaboration networks reveals robust partnerships and suggests areas for potential interdisciplinary research.